A inconstitucionalidade da aplicação imediata da pena no Tribunal do Júri: o conflito aparente entre os princípios da presunção de inocência e soberania dos veredictos - Saltarelli, Pedro Paulo (2024)
In view of the controversy raised in RE 1235340 (Theme 1068) to be appreciate by the Praetorian Excelso, this article sought to make important considerations about the unconstitutionality of the immediate execution of a sentence applied by the Popular Court, discussing the democratic nature of the design of the aforementioned court and conforming it with the constitutional dictates that guide the national accusatory system, in order to establish rights and guarantees whose observance is imperative. In the absence of a peaceful and consolidated position on the subject, we established a comparison between the foundations of those who reject and those who agree with the constitutionality of the device, having as the heart of the discussion the meaning and limit of the principles of presumption of innocence and sovereignty of verdicts, which are in apparent confrontation.